RING finger protein 13 protects against nonalcoholic steatohepatitis by targeting STING-relayed signaling pathways - Lin, Zhibin; Yang, Peijun; Hu, Yufeng; Xu, Hao; Duan, Juanli; He, Fei; Dou, Kefeng; Wang, Lin (Nature communications, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most common liver disorder worldwide. Recent studies show that innate immunity-related signaling pathways fuel NAFLD progression. This study aims to identify potent regulators of innate immunity during NAFLD progression. To this end, a phenotype-based high-content screening is performed, and RING finger protein 13 (RNF13) is identified as an effective inhibitor of lipid accumulation in vitro. In vivo gain- and loss-of-function assays are conducted to investigate the role of RNF13 in NAFLD. Transcriptome sequencing and immunoprecipitation-mass spectrometry are performed to explore the underlying mechanisms. We reveal that RNF13 protein is upregulated in the liver of individuals with NASH. Rnf13 knockout in hepatocytes exacerbate insulin resistance, steatosis, inflammation, cell injury and fibrosis in the liver of diet-induced mice, which can be alleviated by Rnf13 overexpression. Mechanically, RNF13 facilitates the proteasomal degradation of stimulator of interferon genes protein (STING) in a ubiquitination-dependent way. This study provides a promising innate immunity-related target for NAFLD treatment. The STING-relayed inflammation response has been increasingly identified as one of the key drivers of NAFLD progression. Here the authors show that an E3 ubiquitin ligase, RNF13, can ameliorate NAFLD phenotypes by facilitating the TRIM29-mediated degradation of STING.